Disciplinary literacy in religious education: the role and relevance of reading - Unstad, Lars (British Journal of religious education, 2021)
Although religion has played a key role in reading instruction in many education systems, this position has been challenged by increasing religious diversity and the spread of non-religious worldviews. Simultaneously, there has been growing interest in the role of disciplinary literacy in education (i.e. the ways in which a discipline’s knowledge is created, shared and evaluated) as well as the role of the reader. Drawing on classroom observations and interviews in an exploratory study, the article focuses on how adolescents experience reading in religious education (RE). The study shows that students relate meaning-making in RE to developing respect and tolerance, that teachers focus on conceptual understanding while students request a focus on lived religion, and that student meaning-making in RE thrives in a learner-active setting. We discuss the findings in the light of disciplinary reading theory and point towards some disciplinary traditions that should be considered while designing and developing educational practice.